2001
DOI: 10.1074/jbc.m008167200
|View full text |Cite
|
Sign up to set email alerts
|

CRTR-1, a Developmentally Regulated Transcriptional Repressor Related to the CP2 Family of Transcription Factors

Abstract: CP2-related proteins comprise a family of DNA-binding transcription factors that are generally activators of transcription and expressed ubiquitously. We reported a differential display polymerase chain reaction fragment, Psc2, which was expressed in a regulated fashion in mouse pluripotent cells in vitro and in vivo. Here, we report further characterization of the Psc2 cDNA and function. The Psc2 cDNA contained an open reading frame homologous to CP2 family proteins. Regions implicated in DNA binding and olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 58 publications
2
41
0
Order By: Relevance
“…In fact, Drosophila Grainyhead has been implicated both in activation (Bray and Kafatos, 1991;Hayashi et al, 1999) and repression of gene expression. The regions of GET-1 capable of repression are not homologous to the repression domain of LBP-9/CRTR-1, which is located between residues 1-52 (Rodda et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, Drosophila Grainyhead has been implicated both in activation (Bray and Kafatos, 1991;Hayashi et al, 1999) and repression of gene expression. The regions of GET-1 capable of repression are not homologous to the repression domain of LBP-9/CRTR-1, which is located between residues 1-52 (Rodda et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of three mammalian Grainyhead-like genes, CP-2 (Swendeman et al, 1994), LBP-1a (Sueyoshi et al, 1995), and LBP-9 (Huang and Miller, 2000;Rodda et al, 2001), has been characterized, and all are ubiquitously expressed; thus their expression characteristics bear little resemblance to those of Drosophila Grainyhead (Bray et al, 1989;Dynlacht et al, 1989). In contrast, the expression pattern of GET-1, which is prominent in the surface ectoderm and later in epidermis (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3A; Rodda et al, 2001). Characterization of a transcript from the clone 43 trapped allele by 5Ј-RACE demonstrated that a fusion transcript had been generated by a splicing between the splicing donor site at the end of exon 2 of CRTR-1 and the engrailed-2 splicing acceptor in the trap vector.…”
Section: Molecular Characterization Of the Trapped Genesmentioning
confidence: 99%